Zoomorphic Metaphors from a Cognitive Point of View - Sanz Martin, Blanca Elena (Íkala, Revista de Lenguaje y Cultura, 2015)
We are presenting here an analysis of zoomorphism, metaphorical expressions containing nouns referring to humans. The objective is to analyze, from a cognitive linguistics approach, semantic motivations involved in the metaphorical uses of zoomorphism. It will address the effect of prototypicality and frame semantics present in animal lexicon, and metaphorical projection from human dominium to animal dominium.